In vitro Investigation the Antifungal and 940 nm Diode Laser Effects on Inhibition of Candida Albicans Isolated from Oral Cavity - Roaa Osamah Adnan*; Hussein Ali Jawad (Iraqi Journal of Laser, 2023)
Background: Candida albicans is a prevalent commensal that can cause severe health problems in humans. One such condition that frequently returns after treatment is oral candidiasis. Aim: the goal of this research is to evaluate the efficiency of 940 nm as a fungicidal on the growth of Candida albicans in vitro. Material and Methods: In vitro samples (fungal swabs) were taken from the oral cavity of 75 patients suffering from oral thrush. Following the process of isolating and identifying Albicans. The samples are divided into four groups:(Group 1): Suspension of C. albicans was put in a solution of saline as a control group. (Group 2): Suspension of C. albicans that had been treated with nystatin. (Group 3): Suspension of C. albicans was irradiated by diode laser 940 nm at 1 W for 300 seconds in continuous mode. (Group 4): C. albicans suspension was irradiated by laser in a combination of nystatin. ANOVA, Dunnett t, and LSD tests were used to examine the data. A highly significant statistical variation in the count of C. Albicans before and after therapy. Results: The result of this study, finds that the reduction in the CFU/ml in group 4 (laser+nystatin) is highly significant and diode laser has a fungicidal effect on the growth of candida albicans. Conclusion: using a 940 nm diode laser (continuous mode) in a combination of antifungal (nystatin) acts as a fungicidal effect on Candida albicans.